Interpretaciones del delito Para una hermenéutica materialista en la narrativa policial de Juan Carlos Martelli - Feuillet, Lucía (Ariadna Ediciones, 2020)
The main hypothesis of this work is drawn around the category of crime, considered from its place in social productivity, which allows interpretively rewriting some features of the organization of society and its contradictions in the literature.